Activated Carbon from Spent Brewery Barley Husks for Cadmium Ion Adsorption from Aqueous Solution - Ilesanmi Osasona; Kayode Aiyedatiwa; Jonathan Johnson; Oluwabamise Lekan Faboya (Indonesian Journal of Chemistry, 2018)
This study investigated the feasibility of using acid activated carbon prepared from brewery spent barley husks for the adsorption of cadmium from aqueous solution. The effects of operation parameters such as pH, contact time, adsorbent dosage, concentration and temperature were verified. The amount of cadmium adsorbed increased with increase in solution pH, initial solution concentration and with the amount of adsorbent dosed. A time of 5 minutes was required for attainment of equilibrium. The equilibrium data obtained were analysed using both Langmuir and Freundlich isotherm models and the data were better described by Langmuir model with correlation coefficient of 0.9183. The thermodynamic parameters revealed that the removal of cadmium by the activated carbon was exothermic and spontaneous. Thus, activated carbon obtained from brewery spent barley husk can be employed as an economically viable low-cost adsorbent for removing cadmium from aqueous solution.